2009
DOI: 10.1002/cphc.200800579
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling 2D Inter‐ and Intrachain Energy Transfer in Conjugated Polymers

Abstract: The dimensionality of conjugated polymer systems plays an important role in energy-transfer processes, and 1D and 2D energy transfer of excitations are typically much slower than that between pi-stacked chains within a 3D polymeric solid. However, whether 2D energy transfer in conjugated polymers occurs mainly along polymer chains (intrachain), or between in-plain-adjacent polymer chains (interchain), has yet to be determined due to the difficulty of experimentally decoupling inter- and intrachain interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…conclusions have been reported by other research groups [47][48][49]. Beljonne et al assessed both inter-and intra-chain exciton diffusion processes experimentally and theoretically in a polyindenofluorene with a perylene derivative attached to the chain ends (PEC-PIFTEH) 47.…”
mentioning
confidence: 72%
“…conclusions have been reported by other research groups [47][48][49]. Beljonne et al assessed both inter-and intra-chain exciton diffusion processes experimentally and theoretically in a polyindenofluorene with a perylene derivative attached to the chain ends (PEC-PIFTEH) 47.…”
mentioning
confidence: 72%
“…In polymer films excitons migrate along conjugated chains as well as between chains [6][7][8][9][10] . Recent experiments have shown that the coherence length of excitons along perfect and straight chains at cryogenic temperature can be several microns, so that the conjugated chain behaves like a quantum wire 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For white light emissive polymers, doping‐free device architectures can also be developed. Particularly, single polymer incorporated with red‐green‐blue or complementary color emissive species are promising for the development of doping‐free white polymer LEDs . After solving the mentioned issues, doping‐free WOLEDs may exhibit bright prospect for mass production and will play a significant role in the lighting and displays.…”
Section: Discussionmentioning
confidence: 99%